Postkatastroficzne „wypadki języka” - Adamczak, Katarzyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2015)
The subject of review is a collective work Unfälle der Sprache. Literarische und philologische Erkundungen der Katastrophe [“Language Accidents. Literary and Philological Explorations of Catastrophe”] published in 2014 and edited by German Romanicists: Ottmar Ette and Judith Kasper. The book deals with the events recognized as catastrophes and their philological-literary representations. The articles, discussed on the selected examples, depict–on the one hand–a theoretical aspect of struggling with catastrophe itself, as well as with extreme experiences and feelings connected with it. On the other hand, the authors concentrate on the analysis of the literary works dealing with the question of the Shoah, as discussed by Georges-Arthur Goldschmidt, David Grossman, and Jorge Semprún.